2015
DOI: 10.1111/rec.12262
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for evaluating performance of oyster habitat restoration

Abstract: Restoration of degraded ecosystems is an important societal goal, yet inadequate monitoring and the absence of clear performance metrics are common criticisms of many habitat restoration projects. Funding limitations can prevent adequate monitoring, but we suggest that the lack of accepted metrics to address the diversity of restoration objectives also presents a serious challenge to the monitoring of restoration projects. A working group with experience in designing and monitoring oyster reef projects was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 42 publications
2
111
0
1
Order By: Relevance
“…In this study, we used oyster density normalized by reef age for model validation. The utility of an index of normalized density is several-fold: (1) ease of calculation based on values that are often known (i.e., age of restoration) and values that are often collected post-monitoring (i.e., density Powers et al, 2009;Baggett et al, 2015), (2) ability to account for observed peaks and declines in density over time (e.g., Figure 1), and (3) relevance to common density-based restoration targets that can be set over a time period (i.e., 100 oyster m −2 over a 20 year period = normalized density of 2000). Normalized density was a statistically-significant exponential function of HSI, providing validity of the HSI as a robust predictor of suitable habitat for oyster sanctuary restoration in Pamlico Sound.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used oyster density normalized by reef age for model validation. The utility of an index of normalized density is several-fold: (1) ease of calculation based on values that are often known (i.e., age of restoration) and values that are often collected post-monitoring (i.e., density Powers et al, 2009;Baggett et al, 2015), (2) ability to account for observed peaks and declines in density over time (e.g., Figure 1), and (3) relevance to common density-based restoration targets that can be set over a time period (i.e., 100 oyster m −2 over a 20 year period = normalized density of 2000). Normalized density was a statistically-significant exponential function of HSI, providing validity of the HSI as a robust predictor of suitable habitat for oyster sanctuary restoration in Pamlico Sound.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring restoration projects is essential to evaluate the success of restoring degraded ecosystems. Thus, we read with interest and appreciation Baggett et al (), as they suggest a common set of metrics with standardized techniques for judging oyster habitat restoration efficacy regardless of initial project goal(s). As oyster reef construction is a rapidly growing field within restoration ecology, such a “lingua franca” is important from a practitioners point of view as it allows better evaluation of individual projects but also enables scientists to draw comparisons among diverse projects and environmental contexts.…”
Section: Tidal Emersion Included In the Universal Environmental Variamentioning
confidence: 99%
“…; Baggett et al . ). Restoration programmes and research typically use dredged shells or calcium carbonate‐based structures (concrete reef balls, for instance) to create a suitable settlement site for oyster larvae, then either let the natural larval stock settle if present or seed the reef structures from hatchery stock.…”
Section: Shells Returned To the Marine Environmentmentioning
confidence: 97%